VALUE RELEVANCE OF ACCOUNTING INFORMATION BASED ON PSAK CONVERGENCE IFRS (MANUFACTURE FIRMS IN INDONESIA) - Murni Hayati (Jurnal Praktik Bisnis, 2016)
The objective of this research to test Value Relevance Accounting Information based on PSAK Convergence IFRS. Research is done of manufacture firms listed at BEI (2010 until 2013). Sampel in this research is 65 manufacture firms. Variable in this research are Value Relevance Accounting Information before and after PSAK Convergence IFRS. Measured of Value Relevance Accounting Information variable used Earning Per Share (EPS), Book Value Equity Per Share (BVEPS) and Cash Flow From Operation Activities (CFOA). The Paired sampel t-test to know of difference Value Relevance Accounting Information before and after based on PSAK convergence IFRS.The result reveal that indifference Value Relevance Accounting Information of public firms in Indonesia before and after based on PSAK Convergence IFRS .  Keywords :  Value Relevance Accounting Information